The Ecclesial Thinking of «Vida Nueva» Magazine in the Postcouncil Period - Sánchez-Camacho, Jesús (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2020)
As the Church after the Second Vatican Council, Vida Nueva was undergoing a process of profound transformation: in the postconciliar period, the magazine is beginning a journey of renewal by specializing in religious news journalism. This study shows the acceptance of the Council by the magazine and its proposals in ecclesial issues through the results of the analysis of the editorial contents of Vida Nueva from 1968 to 1975. The results reveal that the Conciliar message influences the journal, due to the way it understands and analyses national and international Church events. The publication reflects on the work of Paul VI and the bishops, through the activities and documents published by the Pope, and the work of the dioceses and episcopal conferences. Furthermore, for the magazine, the commitment to renewal includes the involvement of priests, religious and lay people. For this reason, it reflects on themes discussed within the Church such as priestly celibacy, women’s ministries, the responsibility of the laity and secularization. In addition, in order to put the reforms into practice, Vida Nueva is committed to the promotion of new theological currents, the updating of language, the renewal of pastoral methods, the reform of the liturgy, the encouragement of evangelization, the formation of believers, the promotion of social doctrine, the ecumenism and the interfaith dialogue.